Professional Feeding Guidance Improved Infants' Self-Feeding Proportion during Complementary Foods Introduction in Beijing, China: An Exploratory Study - Guochao Song; Jiahui Chang; Hongyan Guan; Yanfeng Zhang; Ting Zhang; Zhaofeng Zhang (MDPI AG, 2023)
An exploratory study was undertaken to examine the prevalence of infants' feeding patterns in Beijing, China, as well as the factors linked to infants' self-feeding proportion during the introduction of complementary foods, and the impact of professional feeding guidance on this proportion. A total of 122 families with infants aged 6-11 months from Beijing were included in the study. A descriptive analysis was employed to assess the prevalence of infants' feeding patterns, while generalized linear model analysis was utilized to investigate the factors associated with these patterns. All families were provided with comprehensive and personalized professional guidance regarding the introduction of complementary foods for infants. However, 64 families were lost to follow-up, leaving 58 families who were re-evaluated and queried after one month. To exclude the influence of infants aging, both the 64 families prior to receiving feeding guidance, and the 58 families after receiving feeding guidance, were included in the analysis. The families with infants aged 6-8 months and 9-11 months were compared separately based on the presence or absence of feeding guidance. Statistical tests, including the Wilcoxon rank-sum test and χ2 test, were conducted to assess any significant differences. The study revealed that the proportion of infants engaging in self-feeding was found to be remarkably low (10% [0%, 40%]). Furthermore, a significant positive association was observed between the proportion of infants engaging in self-feeding and their age (p < 0.001). Notably, after receiving professional feeding guidance, the proportion of infants engaging in self-feeding significantly increased (from 1% [0%, 20%] to 30% [10%, 50%], p < 0.001 for infants aged 6-8 months; from 20% [10%, 50%] to 40% [30%, 50%], p < 0.001 for infants aged 9-11 months). These findings contribute valuable insights for improving postnatal care practices during the introduction of complementary foods for infants.